2011
DOI: 10.1007/s11442-011-0853-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variations of vapor isotope ratios reveal the influence of atmospheric processes

Abstract: Stable isotopes of atmospheric water vapor reveal rich information on water movement and phase changes in the atmosphere. Here we presented two nearly continuous time-series of δD and δ 18 O of atmospheric water vapor (δ v ) measured at hourly intervals in surface air in Beijing and above a winter wheat canopy in Shijiazhuang using in-situ measurement technique. During the precipitation events, the δ v values in both Beijing and Shijiazhuang were in the state of equilibrium with precipitation water, revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
5
25
1
Order By: Relevance
“…Previous research has suggested that large variations of atmospheric water vapor δ D, δ 18 O, and d occur at daily to seasonal time scales, irrespective of whether the surface is covered by vegetation [ Lee et al ., ; Wen et al ., ; Welp et al ., ; Zhang et al ., ; Sunmonu et al ., ; Berkelhammer et al ., ; Farlin et al ., ]. During rainy periods, the water vapor δ D, δ 18 O, and d are primarily influenced by isotopic equilibrium fractionation.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research has suggested that large variations of atmospheric water vapor δ D, δ 18 O, and d occur at daily to seasonal time scales, irrespective of whether the surface is covered by vegetation [ Lee et al ., ; Wen et al ., ; Welp et al ., ; Zhang et al ., ; Sunmonu et al ., ; Berkelhammer et al ., ; Farlin et al ., ]. During rainy periods, the water vapor δ D, δ 18 O, and d are primarily influenced by isotopic equilibrium fractionation.…”
Section: Introductionsupporting
confidence: 92%
“…To our best knowledge, in situ and continuous observations of δ D, δ 18 O, and d of atmospheric water vapor have been performed at approximately 14 sites, with few in inland arid regions. Seven of those sites were in urban or sparse vegetation settings, namely, New Haven, USA, with a humid continental climate [ Lee et al ., ]; Beijing, China, with a rather dry, monsoon‐influenced humid continental climate [ Wen et al ., ; Zhang et al ., ]; Sapporo, Japan, with a humid continental climate characterized by four distinct seasons [ Sunmonu et al ., ]; San Diego, USA, with a Mediterranean climate characterized by warm dry summers and mild winters [ Farlin et al ., ]; Hawaii, USA, with a tropical marine climate [ Noone et al ., ; Hurley et al ., ]; the Greenland Ice Sheet, with an ice cap climate [ Steen‐Larsen et al ., ]; and the Chajnantor Plateau in Chile, with a subtropical desert climate [ Galewsky et al ., ]. The other seven sites were in vegetation‐covered settings, namely, the Great Mountain Forest in the USA, with a humid continental climate [ Lee et al ., , ]; the Wind River Experimental Forest in the USA, with a maritime Pacific climate characterized by dry summer and wet winter periods [ Rambo , ]; the Manitou Experimental Forest in the USA, with a semiarid climate [ Berkelhammer et al ., ]; the mixed evergreen forest located in the Angelo Coast Range Reserve in the USA, with a Mediterranean climate characterized by warm dry summers and cool wet winters [ Simonin et al ., ]; Rosemount soybean site in the USA, with a humid continental climate [ Welp et al ., ; Griffis et al ., , ]; Luancheng winter wheat and summer maize rotation system in China, with a continental, monsoon‐influenced, semiarid climate [ Zhang et al ., ; Wen et al ., 2012b; Xiao et al ., ]; and Dunlun grassland in China, with a dry, monsoon‐influenced, humid continental climate [ Wen et al ., 2012b; Hu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Diurnal water vapor isotope cycles have been widely reported and generally appear to be independent of continentality or vegetation type. Diurnal cycles of δ 18 O and d at UMBS are similar to those observed in coastal New Haven (Lee et al, ; Lee et al, ), above a wheat field (Zhang et al, ) and arid oasis cropland (Huang & Wen, ) in North China, in a coniferous forest in the Pacific Northwest (Lai & Ehleringer, ), above a Mediterranean coastal wetland (Delattre et al, ), in an evergreen forest in Northern California (Simonin et al, ), and in an isotope enabled large‐eddy simulation of the atmospheric boundary layer (Lee et al, ). Welp et al () reported on water vapor d from six sites in the United States and China, including a broadleaf deciduous forest site in Borden, Ontario, near UMBS.…”
Section: Discussionsupporting
confidence: 65%
“…The isotopic composition of precipitation is essential baseline data for various applications. Since the earliest studies by Craig () and Dansgaard (), the isotopic composition of precipitation has been used for various research fields and applications in hydrological processes, such as studies on plant water use (Sugimoto, Yanagisawa, Naito, Fujita, & Maximov, ; Sugimoto et al, ), lake and catchment water balance (Gat, Bowser, & Kendall, ; Gibson & Edwards, ; Ichiyanagi et al, ; Telmer & Veizer, ), groundwater (Deshpande, Bhattacharya, Jani, & Gupta, ; Gupta, Deshpande, Bhattacharya, & Jani, ; Lambert & Aharon, ), and the origin of water vapor (Uemura, Matsui, Yoshimura, Motoyama, & Yoshida, ; Yamanaka & Shimizu, ; Zhang, Sun, Wang, Yu, & Wen, ), as well as in atmospheric science (Gat, ; Risi et al, ; Ueta, Sugimoto, Iijima, Yabuki, & Maximov, ; Ueta et al, ; Winkler et al, ) and paleoclimate reconstruction applications (Chamberlain, Winnick, Mix, Chamberlain, & Maher, ; Jouzel, Merlivat, & Lorius, ; McCarroll & Loader, ; Seki et al, ). Generally, the isotopic composition of precipitation shows a positive correlation with local temperature and a negative correlation with the amount of local precipitation; these are known as the temperature and amount effects, respectively (Araguas‐Araguas, Froehlich, & Rozanski, ; Dansgaard, ; Dayem, Molnar, Battisti, & Roe, ; Wright & Leavitt, ).…”
Section: Introductionmentioning
confidence: 99%